Assessing the state of empirical research on Johnson's typology of violence: a systematic review - Conroy, Nicole E. (Journal of family violence, 2024)
Purpose:To assess the state of empirical research on Johnson’s typology of violence. Method: Using the PRISMA Statement guidelines, we systematically review and critically evaluate peer-reviewed, empirical research studies testing Johnson’s typology, published 1995 to March 31, 2021. Findings: Forty-four studies tested Johnson’s typology using accurate conceptualization and operationalization of the typology. Findings from included studies provided overwhelming support for Johnson’s typology, with only few exceptions. Conclusions: Direct tests of Johnson’s assumptions are necessary for revising and strengthening the utility of the typology. Future research should carefully attend to the conceptual definitions of Johnson’s typology and integrate explicit testing of assumptions throughout study designs.